Prosedur Penanganan Hukum Anak Pelaku Tindak Pidana Narkotika: Perbandingan Hukum Indonesia-Thailand - Sembiring, Kirensi; Abduh, Rachmad (Universitas Muhammadiyah Ponorogo, 2025)
This research aims to explore the sentencing regimes applied to child offenders in the context of narcotic crimes in Indonesia and Thailand, as well as conduct a comparative study on the legal handling procedures applicable in both jurisdictions. Children represent the demographic with the highest prevalence of narcotic use globally. The normative framework in Indonesia is constructed through specific legislative instruments, namely the Republic of Indonesia Law No. 35 of 2009 regarding Narcotics and the Republic of Indonesia Law No. 11 of 2012 governing the Child Criminal Justice System. In the context of Thailand, related regulations are implemented through the Narcotic Act B.E 2522 and Juvenile Court B.E 2494. Narcotic abuse can be perceived as a crime without victim (crime without victim). This terminology indicates that this illegal activity does not produce external suffering, but rather the perpetrator themselves experiences detrimental consequences. This study is a library research with a normative approach, using documentary study methods to collect information and analyzed through qualitative interpretive procedures. The investigation results reveal that the legal regimes in Indonesia and Thailand apply a rehabilitative approach, both through non-institutional and institutional interventions, with the primary focus on protecting the rights of children involved in criminal acts.